Further evidence that singing fosters mental health and wellbeing: the West Kent and Medway project. Issue 1 (13th February 2017) - Clift, Stephen; Manship, Sharon; Stephens, Lizzi
Abstract : Purpose: Clift and Morrison (2011) report that weekly singing over eight months for people with enduring mental health issues led to clinically important reductions in mental distress. The purpose of this paper is to test the robustness of the earlier findings. Design/methodology/approach: Four community singing groups for people with mental health issues ran weekly from November 2014 to the end of 2015. Evaluation place over a six-month period using two validated questionnaires: the short Clinical Outcomes in Routine Evaluation (CORE-10) questionnaire, and the Warwick Edinburgh Mental Wellbeing Scale (WEMWBS). Findings: In all, 26 participants completed baseline and follow-up questionnaires. CORE-10 scores were significantly reduced, and WEMWBS scores significantly increased. Comparisons with the earlier study found a similar pattern of improvements on CORE items that are part of the "problems" sub-scale in the full CORE questionnaire. There was also evidence from both studies of participants showing clinically important improvements in CORE-10 scores. Research limitations/implications: The main limitations of the study are a small sample size and the lack of a randomised control group. Originality/value: No attempts have been made previously to directly test the transferability of a singing for health model to a new geographical area and to evaluate outcomes using the same validated measure.